Decreased benzodiazepine receptor and increased GABA level in cortical tubers in tuberous sclerosis complex - Mori, Kenji; Mori, Tatsuo; Toda, Yoshihiro; Fujii, Emiko; Miyazaki, Masahito; Harada, Masafumi; Kagami, Shoji (Brain & development (Tokyo. 1979), 2012)
To elucidate the functional characteristics of cortical tubers that might be responsible for epilepsy in tuberous sclerosis complex (TSC), proton magnetic resonance spectroscopy (1H-MRS) and [123I] iomazenil (123I-IMZ) single photon emission computed tomography (SPECT) were performed. 1H-MRS using a clinical 3-tesla magnetic resonance imager was performed in four children with TSC and 10 age-and sex-matched healthy control subjects. A single voxel was set on the right parietal lobe in control subjects. In patients with TSC, a single voxel was set on the epileptogenic tuber in the parietal or temporal lobe, and another voxel was set on the contralateral normal-appearing brain region. N-Acetylaspartate (NAA), myo-Inositol (mIns) and Glutamate (Glu) were analyzed using a conventional STEAM (Stimulated Echo Acquisition Mode) method. The concentration of gamma-aminobutyric acid (GABA) was quantified using MEGA-Point Resolved Spectroscopy (PRESS). Interictal 123I-IMZ SPECT was examined in all four patients with TSC. A significant decrease in the NAA concentration and significant increases in the mIns and GABA concentrations were detected in the cortical tubers of all 4 patients. No significant difference was observed in Glu concentrations. In all of the cortical tubers detected by magnetic resonance imaging, 123I-IMZ binding was significantly decreased. Epileptogenesis in TSC might be caused by decreased inhibition secondary to the decrease in GABA receptors in dysplastic neurons of cortical tubers. An increase in the GABA concentration may compensate for decreased inhibition.